Promoting interactions in learning arabic language via learning management system: a theoretical framework - Mohamed Adnan, Mohamad Azrien; Syed Hassan, Sharifah Sariah (Georgian Technical University, 2015)
This paper aims at promoting a framework of interactions among learners, instructors, contents and systems via Learning Management System (LMS).These interactions allow Arabic language learners to bridge their existing knowledge with new information and make new meanings through critical comments among peers, teacher’s feedback and from the interactive learning content. The common interactive activities in LMS include forum, short video, online quizzes and other tools for interactions. The interactive tools embedded in LMS will only promote effective learning through collaboration among learners. Thus, a thorough critical analysis on the theories related to constructivist and social interaction theory will allow teachers to have strategic plans in delivering online teaching and learning. The main advantage of using LMS is the freedom of teachers to add, change or utilize the system according to the individual learning style and learning needs. This paper will elaborate on the proposed design of interactive learning activities forwarded for teachers to enhance their teaching and learning approaches. An in-depth investigation on literature reviews and meta-analysis will underpin the proposed model of interaction tools designed for Arabic Language teaching.